9(x-2)=3(x-2)

Simple and best practice solution for 9(x-2)=3(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(x-2)=3(x-2) equation:


Simplifying
9(x + -2) = 3(x + -2)

Reorder the terms:
9(-2 + x) = 3(x + -2)
(-2 * 9 + x * 9) = 3(x + -2)
(-18 + 9x) = 3(x + -2)

Reorder the terms:
-18 + 9x = 3(-2 + x)
-18 + 9x = (-2 * 3 + x * 3)
-18 + 9x = (-6 + 3x)

Solving
-18 + 9x = -6 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-18 + 9x + -3x = -6 + 3x + -3x

Combine like terms: 9x + -3x = 6x
-18 + 6x = -6 + 3x + -3x

Combine like terms: 3x + -3x = 0
-18 + 6x = -6 + 0
-18 + 6x = -6

Add '18' to each side of the equation.
-18 + 18 + 6x = -6 + 18

Combine like terms: -18 + 18 = 0
0 + 6x = -6 + 18
6x = -6 + 18

Combine like terms: -6 + 18 = 12
6x = 12

Divide each side by '6'.
x = 2

Simplifying
x = 2

See similar equations:

| 4.5x-39=2.2x+7 | | n+n+m=2 | | -3t(4t-4)+8t=3t-4 | | 7x+4=x+10 | | x=y/6(16-z) | | -27x^2+48x-5= | | 4(t-3)=2t+7 | | -2(3t-4)+3t=2t-3 | | -27x^3+48x-5= | | 10x^2+2.5x-45=0 | | 3x+11=6x-4 | | 5+6=5+x | | 6x^2-4x=-11 | | 8+y=6+2y | | -5(3t-2)+2t=4t-9 | | x^4-8x^3+98x^2-648x+1377=0 | | 36m^-4n^-6/4mn^-2p^-4 | | -x^2-100=0 | | 19=4-2m-m+7 | | (2x+4)+(3x-13)=180 | | 20a+25= | | 12-4y=2(y+9) | | 2.50x=500+0.35x | | 16a+28= | | 150x+50y=8395 | | (2a/a^2)^-2 | | 50(x+5)=a | | 200x+100y=12995 | | 3k(3k+10)=0 | | (2a/a^2)^2 | | 5x-2x=x+30 | | 3x-2=5x-19 |

Equations solver categories